Specific tumor-derived CCL2 mediated by pyruvate kinase M2 in colorectal cancer cells contributes to macrophage recruitment in tumor microenvironment - Kejian Zou; Yaodong Wang; Yan Hu; Liansheng Zheng; Wanfu Xu; Guoxin Li (Tumor Biology)
Development of colorectal cancer has been considered as a result of imbalance of pro- and anti-inflammatory intestinal microenvironment accompanied by macrophage recruitment. Despite macrophages are implicated in remodeling tumor microenvironment, the mechanism of macrophage recruitment is not fully elucidated yet. In this study, we reported clinical association of highly expressed pyruvate kinase M2 in colorectal cancer with macrophage attraction. The conditioned medium from Caco-2 and HT-29 cells with depleted pyruvate kinase M2 dramatically reduced macrophage recruitment, which is reversed by addition of, a critical chemotaxis factor to macrophage migration, rCCL2. Silencing of endogenous pyruvate kinase M2 markedly decreased CCL2 expression and secretion by real-time quantitative polymerase chain reaction and enzyme-linked immunosorbent assay. Endogenous pyruvate kinase M2 interacted with p65 and mediated nuclear factor-κB signaling pathway and mainly regulated phosphorylation of Ser276 on p65 nuclear factor-κB. In addition, inhibition of macrophage recruitment caused by pyruvate kinase M2 silencing was rescued by ectopic expression of p65. Interestingly, pyruvate kinase M2 highly expressed in colorectal cancer tissue, which is correction with macrophage distribution. Taken together, we revealed a novel mechanism of pyruvate kinase M2 in promoting colorectal cancer progression by recruitment of macrophages through p65 nuclear factor-κB–mediated expression of CCL2.